THE EFFECT OF FINGER PAINTING ON THE DEVELOPMENT OF CHILDREN’S CREATIVITY - Zikra Hayati; Heliati Fajriah; Nida Jarmita; Wati Oviana; Riska Ovalia (Bunayya, 2024)
Based on the results of observations carried out at PAUD Ceria in August 2023, it was found that there were children aged 5-6 years who had problems with the development of creativity which were identified when the children were not able to complete the drawing task with the free theme given, when the drawing activity was in progress. progressing, the child does not look enthusiastic, and the child will imitate the example of the teacher's drawing shown, the child is not yet able to create different work from his friends. This research aims to find out whether there is an influence of finger painting in developing the creativity of children aged 5-6 years at PAUD Ceria Sabena Kids II Aceh Besar. The research uses a quantitative type with experimental methods, research design "Pre-test and Post-test one group designs". The population in this study was 46 children and the sample was 26 children using purposive sampling technique. The results of this research obtained a pretest score of 57.38 and a post-test of 74.42, the significance value obtained in the normality test in the pretest was 0.066 > 0.0, in the posttest 0.002 > 0.05 it can be stated that the two data are normally distributed. The obtained value of tcount > ttable is 8.8 > 1.708, thus there is a rejection of Ho and acceptance of Ha, which means that there is an influence of finger painting on the development of creativity in children aged 5-6 years at PAUD Ceria.